Tratamiento adecuado de la insuficiencia cervical - Andrade Illescas, Ghislaynne Leonor (Machala : Universidad Técnica de Machala, 2024)
Introduction: Cervical incompetence (CI), also known as cervical insufficiency, is a significant obstetric condition that can trigger recurrent miscarriage and preterm delivery, may be present in approximately 1% of obstetric populations. The purpose of this study is to examine the therapeutic alternatives indicated for this condition by analyzing high impact articles in women of childbearing age for timely management in the professional setting. Materials and methods: A descriptive, observational and retrospective study was carried out, using the bibliographic method, where different scientific articles, case reports, clinical guides obtained from platforms such as Pubmed, Scielo, Google Scholar, Elsevier, among others, were consulted. Results: The results obtained show that, in patients with a high risk of presenting preterm labor, cerclage reduces the occurrence of preterm labor in relation to expectant management. This indicates that cerclage may be a safe intervention to reduce the risk of preterm delivery in women with obstetric history or risk factors predisposing to cervical insufficiency. Conclusion: Due to the complexity and severity of HF, it is critical that research continues to increase understanding of this condition and to create favorable diagnostic and treatment strategies. This includes exploring new therapeutic modalities such as progesterone, the use of pessaries, and other interventions that may help prevent adverse outcomes associated with HF, such as miscarriage and preterm delivery.
Introducción: La incompetencia cervical (IC), también conocida como insuficiencia cervical, es una condición obstétrica significativa que puede desencadenar abortos recurrentes y partos prematuros, puede estar presente en aproximadamente 1% de las poblaciones obstétricas. El propósito de este estudio es examinar las alternativas terapéuticas indicadas para esta enfermedad mediante el análisis de artículos de alto impacto en mujeres de edad fértil para un manejo oportuno en el ámbito profesional. Materiales y métodos: sé efectuó un estudio descriptivo, observacional y retrospectivo, haciendo uso del método bibliográfico, donde se consultaron diferentes artículos científicos, reporte de casos, guías clínicas obtenidas de plataformas como Pubmed, Scielo, Google académico, Elsevier entre otros. Resultados: Los resultados obtenidos muestran que, en pacientes con un elevado riesgo de presentar parto prematuro, el cerclaje disminuye la aparición de parto prematuro en relación con el manejo expectante. Esto indica que el cerclaje puede ser una intervención segura para aminorar el riesgo de parto prematuro en mujeres con antecedentes obstétricos o factores de riesgo que predisponen a la insuficiencia cervical. Conclusión: Debido a la complejidad y gravedad de la IC, es fundamental que la investigación continúe para aumentar la comprensión de esta condición y para crear estrategias de diagnóstico y tratamiento favorables. Esto incluye explorar nuevas modalidades terapéuticas como la progesterona, el uso de pesarios y otras intervenciones que puedan ayudar a prevenir los resultados adversos asociados con la IC, como los abortos espontáneos y los partos prematuros.
Keywords: CUELLO UTERINO; CONTRACCION UTERINA; MEMBRANA AMNIOTICA; CERCLAJE CERVICAL